Design of Light Intensity Control Device based on LED Matrix Control Wireless Lamp - Ambotang, Geri Renalda; Widodo, Nuyono Satya (Buletin Ilmiah Sarjana Teknik Elektro, 2021)
This research make a wireless lamp light intensity regulator device based on LED matrix control. The device regulates lamp light intensity that is conform with the eating, sleeping, reading, using a laptop activities based on the existing provisions in SNI 03-6575-2001. The Arduino Uno ATMega328 microcontroller used to control the number of LED lamps that are light up to adjust the intensity of the light that fall upon the surface (lux) according to the activity that selected by user's smartphone. The BH1750 sensor will detect the light intensity produced by the lamp as information of the lamp light intensity condition. This research has been completed and succeeded in making a wireless lamp light intensity regulator device based on LED Matrix Control which can adjust the lamp light intensity of the lamp conform with the activities that the user want to do according to SNI 03-6575-2001. The device has been successfully created with an error percentage of 1.33% on examination with four different types of activities with total of 20 trials.Penelitian ini membuat alat pengatur intensitas cahaya lampu nirkabel berbasis kendali matriks LED. Alat mengatur intensitas cahaya lampu dengan menyesuaikan pada kegiatan makan, tidur, membaca, menggunakan laptop berdasarkan ketentuan yang ada pada SNI 03-6575-2001. Mikrokontroler ATMega328 Arduino Uno digunakan untuk mengendalikan jumlah lampu LED yang menyala guna mengatur intensitas cahaya yang akan jatuh ke permukaan (lux) menyesuaikan dengan kegiatan yang dipilih melalui smartphone pengguna. Sensor BH1750 akan mendeteksi intensitas cahaya yang dihasilkan oleh lampu sebagai informasi kondisi intensitas cahaya lampu. Penelitian ini sudah selesai dilakukan dan berhasil membuat Alat Pengatur Intensitas Cahaya Lampu Nirkabel berbasis Kendali Matriks LED yang dapat mengatur intensitas cahaya lampu berdasarkan kegiatan yang akan dilakukan pengguna menyesuaikan SNI 03-6575-2001. Alat telah berhasil dibuat dengan persentase error 1,33% pada pengujian terhadap empat jenis kegiatan yang berbeda dengan total 20 kali percobaan.